2019
DOI: 10.1523/eneuro.0266-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Maturation of Olfactory Sensory Neurons in the Mature Olfactory Epithelium

Abstract: The formation of the olfactory nerve and olfactory bulb (OB) glomeruli begins embryonically in mice. However, the development of the olfactory system continues throughout life with the addition of new olfactory sensory neurons (OSNs) in the olfactory epithelium (OE). Much attention has been given to the perinatal innervation of the OB by OSN axons, but in the young adult the process of OSN maturation and axon targeting to the OB remains controversial. To address this gap in understanding, we used BrdU to label… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
55
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 67 publications
4
55
0
1
Order By: Relevance
“…The costaining results showed that the BrdU + /GAP43 + cells accounted for 18.30 AE 0.7709% of the total GAP43 + cells in the NC mice ( Fig 4D and E). The results were consistent with previous studies (Coleman et al, 2017;Liberia et al, 2019). However, in the MOE of the miR-200b/a KD mice, the number of BrdU + /GAP43 + cells was only 1.007 AE 0.1217% of the GAP43 + cells (Fig 4D and E).…”
supporting
confidence: 93%
See 2 more Smart Citations
“…The costaining results showed that the BrdU + /GAP43 + cells accounted for 18.30 AE 0.7709% of the total GAP43 + cells in the NC mice ( Fig 4D and E). The results were consistent with previous studies (Coleman et al, 2017;Liberia et al, 2019). However, in the MOE of the miR-200b/a KD mice, the number of BrdU + /GAP43 + cells was only 1.007 AE 0.1217% of the GAP43 + cells (Fig 4D and E).…”
supporting
confidence: 93%
“…For analysis of differentiation of GBCs, male mice (NC and miR-200 KD, n = 3 mice each group, 12-14 weeks old) were injected with BrdU twice (with intervals of 2 h). Tissues were collected 3 days after BrdU injection (Liberia et al, 2019).…”
Section: Brdu and Edu Lineage Tracingmentioning
confidence: 99%
See 1 more Smart Citation
“…Two groups of stem cells exist in the OE, the quiescent horizontal basal cells which serve as a reserve stem cell population that activates following severe OE injury, and the actively cycling globose basal cells which are the primary progenitor for OSN renewal and recovery following minor injury (Schwob et al, 2017). The development of new OSN takes roughly 10 days as marked by both expressions of mature OSN markers and glomeruli innervation (Liberia et al, 2019). One challenge inherent in this process is the need to constantly rewire the OE to the OB.…”
Section: Dealing With Damage Through Renewalmentioning
confidence: 99%
“…To determine whether FAK inhibition-induced CNTF affects neuronal differentiation, the FAK14 and BrdU treatments were followed (pulse-chase method) by 9 and 20 days before analyses. This extended period allows for basal stem cells to proliferate and differentiate into mature OSNs, a process that takes 10–20 days ( Schwob et al, 1995 ; Jia et al, 2009 ; Liberia et al, 2019 ). To analyze the fate of FAK14-induced GBC proliferation, BrdU-positive nuclei in the total olfactory epithelium, middle OSN layer and basal stem cell layer were counted.…”
Section: Resultsmentioning
confidence: 99%